PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI PENDEKATAN GUIDED DISCOVERY UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF - Anna Roosyanti (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
This research aims to develop Guided Discovery based teaching learning package to facilitate the critical and creative thinking skills. These teaching learning package were implemented in two phases, namely the development of the model 4-P (4-D Models) and the implementation on 30 students of VII grade of Mujahidin Junior High School of Surabaya, using one group pretest-posttest design. Data was analyzed descriptively quantitative and qualitative. The results showed that Guided Discovery based teaching learning package valid and good, critical and creative thinking skills increased. Validation result are for RPP 3.87, LKS 3.87, students book 3.59, learning outcomes test 3.87, critical thinking skills test 3.64, thinking critical and creative skills assessment form 3.63. The students mastery of learning outcomes was with proportion of 80,70%. Based on the data it can be concluded that the Guided Discovery based teaching learning package can improve students critical and creative thinking skills, and to improve students mastery of learning outcomes. Keywords: Creative Thinking Skills, Critical Thinking Skills, Guided Discovery.